Analysis and cloning of CP 1102 gene isolated from a medicinal plant - Mubeen, Hira; Raza, Shahid (International Journal of Biological Research, 2017)
Calotropis procera is a common medicinal plant with various properties related with its latex which functions as a rich source of biologically active compounds. Latex is chemically diverse and the chemical and biochemical differences are considerable for different plant fluids. This plant can produce large quantity of latex. The study was performed to clone the CP1102 terminator region of gene in general expression vector PTZ57R/T. The objective was to make a variant of pJITT166 (size 5.8kb) containing CP1102 terminator sequence to study different expression levels in future. The fragment of 341bp size was isolated. The pDNOR vector containing CP1102 terminator sequence was isolated and amplified by PCR. The forward and reverse primer specific to CP1102 terminator sequence which can amplify this sequence are designed by using bioinformatics tools.